2011
DOI: 10.1186/1756-0500-4-554
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR quantification of the canine filaggrin orthologue in the skin of atopic and non-atopic dogs: a pilot study

Abstract: BackgroundCanine atopic dermatitis (AD) is a common inflammatory skin disease associated with defects in the epidermal barrier, particularly in West Highland white terriers (WHWTs). It shares many similarities with human AD, and so may be a useful animal model for this disease. Epidermal dysfunction in human AD can be caused by mutations in the gene encoding the epidermal protein filaggrin (FLG) and, in some atopic patients, be associated with altered FLG mRNA and protein expression in lesional and/or non-lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…It has been reported that canine atopic skin has increased degradation of ceramides due to increased enzymatic activity. The same may be true for increased degradation of proteins, such as filaggrin, explaining why most studies in atopic dogs have failed to identify a genetic mutation in the filaggrin gene . It is also known that an increased cutaneous pH in atopic skin induces an increase in the activity of proteases, which may result in excessive degradation of proteins, including filaggrin.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that canine atopic skin has increased degradation of ceramides due to increased enzymatic activity. The same may be true for increased degradation of proteins, such as filaggrin, explaining why most studies in atopic dogs have failed to identify a genetic mutation in the filaggrin gene . It is also known that an increased cutaneous pH in atopic skin induces an increase in the activity of proteases, which may result in excessive degradation of proteins, including filaggrin.…”
Section: Discussionmentioning
confidence: 99%
“…The same may be true for increased degradation of proteins, such as filaggrin, explaining why most studies in atopic dogs have failed to identify a genetic mutation in the filaggrin gene. 24,25 It is also known that an increased cutaneous pH in atopic skin induces an increase in the activity of proteases, 7 which may result in excessive degradation of proteins, including filaggrin. Another explanation could be the increased activity of anti-proteases, which does not allow the degradation of profilaggrin into filaggrin monomers, as recently reported in people with AD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations